γδ T Cells and Tumor Microenvironment: From Immunosurveillance to Tumor Evasion - Lo Presti, Elena; Pizzolato, Gabriele; Corsale, Anna Maria; Caccamo, Nadia; Sireci, Guido; Dieli, Francesco; Meraviglia, Serena (Frontiers in Immunology, 2018)
gamma delta T cells possess cytotoxic anti-tumor activity mediated by production of pro-inflammatory cytokines, direct cytotoxic activity and regulation of the biological functions of other cell types. Hence, these features have prompted the development of therapeutic strategies in which gamma delta T cells- agonists or ex vivo-expanded gamma delta T cells are administered to tumor patients. Several studies have shown that gamma delta T cells are an important component of tumor-infiltrating lymphocytes in patients affected by different types of cancer and a recent analysis of ~18,000 transcriptomes from 39 human tumors identified tumor-infiltrating gamma delta T cells as the most significant favourable cancer-wide prognostic signature. However, the complex and intricate interactions between tumor cells, tumor microenvironment and tumor-infiltrating immune cells results in a balance between tumor-promoting and tumor-controlling effects and gamma delta T cells functions are often diverted or impaired by immunosuppressive signals originating from the tumor microenvironment. This review focuses on the dangerous liason between gamma delta T cells and tumoral microenviroment and raises the possibility that strategies capable to reduce the immunosuppressive environment and increase the cytotoxic ability of gamma delta T cells may be the key factor to improve their utilization in tumor immunotherapy.